POLYMORPHISM OF GENES FOR SOMATOTROPIN, PROLACTIN, LEPTIN, AND THYROGLOBULIN IN STUD BULLS - S. V. Tjulkin; T. M. Ahmetov; E. F. Valiullina; R. R. Vafin (Вавиловский журнал генетики и селекции, 2014)
We have studied the polymorphism of genes for somatotropin (GH), prolactin (PRL), leptin (LEP), and thyroglobulin (TG) in thoroughbred and hybrid Holstein stud bulls. Our results are in agreement with data from the literature. The frequencies of alleles in the bulls examined are: L = 0.86 and V = 0.14 in GH, A = 0.87 and B = 0.13 in PRL, C = 0.59 and Т = 0.41 in LEP, C = 0.81 and Т = 0.19 in TG.